Terrorism and the politics of fear - Altheide, David L. (AltaMira, 2006)
Introduction -- Social reality of fear -- The mass media as a social institution -- Crime and terrorism -- Consuming terrorism -- Terrorism and the politics of fear -- The control narrative of the Internet -- The propaganda project and the Iraq War -- Constructing Pat Tillman -- Conclusion: Beyond the politics of fear.